Discrepancies in breast cancer’s oncological outcomes between public and private institutions in the southeast region of Brazil: a retrospective cohort study - Andrade, Diocésio Alves Pinto; Veneziani, Ana Carolina; Paiva, Carlos Eduardo; Reis, Ricardo dos; Filho, Carlos Alberto Fruet; Sanches, André Octávio Nicolau; Barroso, Alison Wagner Azevedo; Paz, Alessandra Caroline Moretto Carbinatto; Kons, Georgia Cristina de Mello; Preto, Daniel D’Almeida; Budib, Maria Carolina Bogoni; Safro, Maria Augusta; et al. (Frontiers in Oncology, 2023)
Background: Brazil is a middle-income country with inequalities in its health care system. The disparities between public and private services affect diagnosis and treatment of patients with breast cancer. The aim of this study is to assess whether the disease-free survival (DSF) and overall survival (OS) are different in public and private specialized centers. Patient and Methods: A retrospective cohort study with 1545 breast cancer patients diagnosed from 2003 to 2011 among Barretos Cancer Hospital – BCH (Public Group, N=1408) and InORP Oncoclinicas (Private Group N=137) was conducted. A 1:1 propensity score matching (PSM) analysis was used to adjust the differences between the group’s characteristics (n=137 in each group). Results: Median age at diagnosis was 54.4 years. Estimated DFS at 1 year, 5 years, and 10 years were 96.0%, 71.8%, and 59.6% at BCH and 97.8%, 86.9%, and 78% at INORP, respectively (HR: 2.09; 95% confidence interval [CI], 1.41 to 3.10; P<0.0001). Estimated OS at 1 year, 5 years, and 10 years were 98.1%, 78.5%, and 65.4% at BCH and 99.3%, 94.5%, and 91.9% at INORP, respectively (HR: 3.84; 95% confidence interval [CI], 2.16 to 6.82; P<0.0001). After adjusting by PSM, DFS and OS results in 1 year, 3 years, and 5 years remained worse in the public service compared to private one. Conclusion: Patients treated in a public center have worse DFS and OS after a follow-up period more than 5 years. These results are corroborated after carrying out the PSM.